Teacher Social Competence and Parent Satisfaction Correlation in Primary Schools: Korelasi Antara Kompetensi Sosial Guru dan Kepuasan Orang Tua di Sekolah Dasar - silvia putri ramadhani; ), Mahardika Darmawan Kusuma Wardana (Academia Open, 2025)
General Background: Teacher professionalism in primary education includes social competence that supports communication and collaboration with parents as key stakeholders. Specific Background: Classroom teachers are expected to interact effectively with families, yet parental satisfaction is often shaped by direct service experiences rather than internal professional practices. Knowledge Gap: Previous studies rarely examine the direct quantitative association between teachers’ social competence and parent satisfaction at the elementary level. Aims: This study analyzes the relationship between classroom teachers’ social competence and parents’ satisfaction in a public primary school context. Results: Using a quantitative correlational design with Spearman Rank analysis involving 15 parents and internal teacher assessments, the correlation coefficient was 0.280 (p = 0.285), indicating a positive but weak and statistically insignificant relationship. Descriptive findings show teachers demonstrate adequate communication, collaboration, and parental involvement, while satisfaction is primarily shaped by personal communication, attention to children, and classroom services. Novelty: The study provides direct measurement of the correlation between social competence dimensions and parental perceptions within a specific elementary school setting. Implications: Findings suggest that professional development should prioritize visible, parent-centered communication practices alongside internal collaboration to align teacher competence with stakeholder expectations. Keywords :  Teacher Social Competence, Parent Satisfaction, Elementary School, Spearman Rank, Educational Service Quality Key Findings Highlights: Parents reported high approval of classroom interaction and information clarity Professional networking participation remained limited among educators Statistical association between measured variables categorized as low